Effect of different levels of nitrogen and leaf cutting on leaf and seed yield of coriander (Coriandrum sativum) - K K Thakral, S K Tehlan, (Journal of Spices and Aromatic Crops, 2008)
The effect of different levels of nitrogen (30, 60, 90 and 120 kg N/ha) and leaf cutting (no cutting, one cutting at 45 days after sowing) and two cuttings at 45 and 60 days after sowing of coriander (Coriandrum sativum L.) cv. DH-228 was studied during 2003-04 and 2004-05. Both green leaf yield and seed yield increased with the increase in N levels upto 90 kg /ha. Single leaf cutting at initial vegetative growth stage did not much affect the later vegetative and reproductive growth. Maximum seed yield was recorded with 90 kg N/ha (14.6 q/ha) without leaf cutting which was at par with 90 kg N/ha and one cut (14.2 q/ha). The green leaf yield was recorded highest with 90 kg N/ha and two cutting (186.4 q/ha).